Sea turtle strandings, sightings and accidental catch along the Croatian Adriatic coast - HAMA, FEITOUMATT LEMATT; KARAICA, DEAN; KARAICA, BOJAN; RODIĆ, PETRA; JELIĆ, KATJA; MAHEČIĆ, IVANA; JELIĆ, DUŠAN (Mediterranean Marine Science, 2020)
The northern Adriatic Sea has long been known as the foraging and developmental habitat of loggerhead sea turtles. Previous literature on stranded, floating, sighted, and accidentally caught sea turtles is fragmentary and mainly obtained from this shallower northern part. This work presents data on 272 records of stranded, floating, sighted and accidentally captured turtles within the entire Croatian Adriatic. The data was collected through the national stranding network for strictly protected marine species run by the Croatian Agency for the Environment and Nature during a six-year period (2010-2015). We focused on analysing spatial and temporal observations, age structure, and reporting sources. The collected morphometric data revealed that most measured C. caretta (85%) were immature individuals found stranded and floating at sea. These observations were location-dependent with a tendency towards the shallow northern areas (≤200 m). Most of the stranded individuals were severely decomposed preventing the determination of possible mortality causes. Most non-decomposed individuals had fishery- or boat-inflicted mechanical injuries confirming fishing activities and boat collisions as threats to young C. caretta individuals in the Croatian Adriatic Sea. Results also revealed an important contribution of local people in reporting the C. caretta strandings and sightings whereas most accidentally caught individuals were reported by unknown sources. Altogether, the data presented in this paper indicate possibilities for improving the ongoing sea turtle monitoring and conservation activities along the entire Croatian Adriatic coast.